Sinologiczne tropy w dwóch powieściach Teodora Parnickiego - Bourkane, Mateusz (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
As the title suggests, the article focuses on Chinese traces and motifs in Teodor Parnicki’s prose. The considerations pertain to his historical novels Koniec “Zgody Narodów” and Słowo i ciało where the Chinese elements create extremely specific philosophical and cultural contexts. The analysis revolves around the contacts between ancient Chinese kingdoms and the Asian Hellenistic monarchies mentioned in both novels. As a result of the analysis, Parnicki is presented as a writer attempting to capture the psychological phenomenon of an individual meeting with the paradigm of a mysterious, highly distant civilisation.